PEMBENTUKAN KARAKTER DISIPLIN PESERTA DIDIK MELALUI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SMA BUDI UTOMO PERAK - Wahyudi Wahyudi; Khoirun Nisa’; Fahmi Fachrurrozie (Muróbbî: Jurnal Ilmu Pendidikan, 2023)
Discipline character is a fundamental value that builds personality. Discipline character education in Indonesia has become a necessity that cannot be avoided. Reviewing the National Education System Law in Indonesia, education is a process to produce graduates who are noble, professional in the field of science and technology and able to adapt in society. This study aims to identify; (1) the formation of the character of student discipline through learning Islamic religious education at SMA Budi Utomo Perak (2) the problems and their solutions. This research was conducted at SMA Budi Utomo Perak where this school upholds the values ??of the character of the religious profession, excellence, solidarity, trustworthiness, virtue, skill and independence in its vision. Researchers use qualitative research as a method. The research subjects were vice principals for curriculum, Islamic religious education teachers, and several students. Data collection techniques used are observation, interviews, and documentation. The results of this study indicate that the teaching of disciplinary character through Islamic religious education is quite effective starting from teaching planning, implementing the teaching process, and teaching evaluation.